2016
DOI: 10.1007/978-3-319-33714-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the Dahl Model Applied to Modelling of Static Friction in Closed-Loop Kinematic Chains

Abstract: High parametric sensitivity of the Dahl model is observed when rigid body approach is used to analyse the static friction in close-loop mechanisms. The origins of sensitivity problems are investigated. The possibility of diminishing sensitivity problems by taking flexibility into account is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…In each case, it was shown that rigid-body models of multibody systems offer no means to credibly predict friction forces in the stiction regime and its vicinity. Note that most recent studies show that similar effects are observed also for the Dahl model [42].…”
Section: Discussionsupporting
confidence: 74%
“…In each case, it was shown that rigid-body models of multibody systems offer no means to credibly predict friction forces in the stiction regime and its vicinity. Note that most recent studies show that similar effects are observed also for the Dahl model [42].…”
Section: Discussionsupporting
confidence: 74%
“…These models are data-driven ones that do not consider physical sources of actuator-based hysteresis, and they can be approximately classified into general mathematics-based models, differentialbased models and operator-based models. General mathematics-based models fit hysteresis loops by testing common mathematical functions such as polynomial functions, exponential functions or trigonometric functions [14,15]; Differential-based models adopt nonlinear differential equations to display the hysteresis, such as Dahl model [16], Duhem model [17], Bouc-Wen [18] model and LuGre model [19]. Although differential-based models provide several advantages like compact structures and easy-to-use controller design, these models have difficulties in identifying complex parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies [7,8] it was shown that problems with uniqueness of solution may be experienced when closed-loop mechanisms without redundant constraints are modeled and simulated. The investigation was focused on the stiction phase and its neighborhood, when the relative joint velocities are null or close to zero.…”
Section: Introductionmentioning
confidence: 99%